2020
DOI: 10.1049/iet-epa.2020.0390
|View full text |Cite
|
Sign up to set email alerts
|

Influence of design parameters on flux‐weakening performance of interior permanent magnet machines with novel semi‐overlapping windings

Abstract: This study performs a design and parametric study of interior permanent‐magnet (IPM) machines equipped with novel semi‐overlapping windings (NSWs). The influence of the key design parameters including; number of turns per phase, stack length, distance and angle between V‐shaped magnets, rotor yoke thickness, magnetic bridge width and thickness and number of magnet segments on the flux‐weakening (FW) performance characteristics are evaluated in detail. The influence of material of segmentation (material of brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…For the FW calculations, the dq equivalent circuit of the IPM machine is employed. More details about the FW algorithm employed in this study can be found in [41].…”
Section: Design Specifications and Analysis Methodsmentioning
confidence: 99%
“…For the FW calculations, the dq equivalent circuit of the IPM machine is employed. More details about the FW algorithm employed in this study can be found in [41].…”
Section: Design Specifications and Analysis Methodsmentioning
confidence: 99%
“…When phase current has a phase advance angle in comparison to the q-axis, the d-axis current 𝑖 𝑑 acts as a weakening current. Thus, the motors are controlled by maximum torque-per-ampere (MTPA) mode below corner speed and flux-weakening control mode above the corner speed [30] 𝑉 𝑑 2 + 𝑉 𝑞 2 ≤ 𝑢 𝑚𝑎𝑥 2…”
Section: Flux-weakening Capabilitiesmentioning
confidence: 99%
“…The simulation is repeated at 3x rated speed to observe impacts when moving into field-weakening (FW) operation. The stranded design needs the largest amount of FW as it has higher air gap flux density, which requires more negative daxis current to counteract [26]. When increasing the speed, the efficiency trend changes, as edgewise PS is most efficient.…”
Section: Operating Point Analysismentioning
confidence: 99%